Alteration of the gene expression profile of T-cell receptor αβ-modified T-cells with diffuse large B-cell lymphoma specificity. (1st May 2013) - Zha, Xianfeng; Yin, Qingsong; Tan, Huo; Wang, Chunyan; Chen, Shaohua; Yang, Lijian; Li, Bo; Wu, Xiuli; Li, Yangqiu
Abstract : Antigen-specific, T-cell receptor (TCR)-modified cytotoxic T lymphocytes (CTLs) that target tumors are an attractive strategy for specific adoptive immunotherapy. Little is known about whether there are any alterations in the gene expression profile after TCR gene transduction in T cells. We constructed TCR gene-redirected CTLs with specificity for diffuse large B-cell lymphoma (DLBCL)-associated antigens to elucidate the gene expression profiles of TCR gene-redirected T-cells, and we further analyzed the gene expression profile pattern of these redirected T-cells by Affymetrix microarrays. The resulting data were analyzed using Bioconductor software, a two-fold cut-off expression change was applied together with anti-correlation of the profile ratios to render the microarray analysis set. The fold change of all genes was calculated by comparing the three TCR gene-modified T-cells and a negative control counterpart. The gene pathways were analyzed using Bioconductor and Kyoto Encyclopedia of Genes and Genomes. Identical genes whose fold change was greater than or equal to 2.0 in all three TCR gene-redirected T-cell groups in comparison with the negative control were identified as the differentially expressed genes. The differentially expressed genes were comprised of 33 up-regulated genes and 1 down-regulated gene including JUNB, FOS, TNF, INF-γ, DUSP2, IL-1B, CXCL1, CXCL2, CXCL9, CCL2, CCL4, and CCL8. These genes are mainly involved in the TCR signaling, mitogen-activated protein kinase signaling, and cytokine-cytokine receptor interaction pathways. In conclusion, we characterized the gene expression profile of DLBCL-specific TCR gene-redirected T-cells. The changes corresponded to an up-regulation in the differentiation and proliferation of the T-cells. These data may help to explain some of the characteristics of the redirected T-cells.